2023
DOI: 10.15252/embj.2022112094
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐PKcs and ATM modulate mitochondrial ADP‐ATP exchange as an oxidative stress checkpoint mechanism

Abstract: DNA-PKcs is a key regulator of DNA double-strand break repair. Apart from its canonical role in the DNA damage response, DNA-PKcs is involved in the cellular response to oxidative stress (OS), but its exact role remains unclear. Here, we report that DNA-PKcs-deficient human cells display depolarized mitochondria membrane potential (MMP) and reoriented metabolism, supporting a role for DNA-PKcs in oxidative phosphorylation (OXPHOS). DNA-PKcs directly interacts with mitochondria proteins ANT2 and VDAC2, and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…suggesting that impairments to these ATM-regulated DNA damage response pathways do not cause mitochondrial defects in this cell type. This aligns with the premise that mitochondrial impairments and oxidative stress in ATM deficient cells are not merely a downstream result of accumulating nuclear DNA damage [20,67].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…suggesting that impairments to these ATM-regulated DNA damage response pathways do not cause mitochondrial defects in this cell type. This aligns with the premise that mitochondrial impairments and oxidative stress in ATM deficient cells are not merely a downstream result of accumulating nuclear DNA damage [20,67].…”
Section: Discussionsupporting
confidence: 80%
“…These findings are of particular interest, as previous studies showed that AT ONS cells possess neuronal-like features and exhibit hypersensitivity to radiation, defective radiation-induced signalling and cell cycle checkpoint defects [26], suggesting that impairments to these ATM-regulated DNA damage response pathways do not cause mitochondrial defects in this cell type. This aligns with the premise that mitochondrial impairments and oxidative stress in ATM deficient cells are not merely a downstream result of accumulating nuclear DNA damage [20, 67].…”
Section: Discussionsupporting
confidence: 78%
“…DNA-PKcs can directly interact with mitochondrial proteins ANT2 and VDAC2. The resulting DNA-PKcs/ANT2/VDAC2 (DAV complex) regulates mitochondrial ADP–ATP exchange and OXPHOS, thereby accelerating cellular oxidative stress repair [ 119 ].…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…The accessory factors APLF and WRN were identified, and several other proteins thought to be involved in regulating NHEJ (e.g., MRE11). We also discovered a rich complement of mitochondrial proteins that have only recently been uncovered . Many of the proteins that we detected are anticipated to be novel binders or substrates of DNA-PKcs, but this will require extensive biological validation.…”
Section: Resultsmentioning
confidence: 94%
“…We also discovered a rich complement of mitochondrial proteins that have only recently been uncovered. 45 Many of the proteins that we detected are anticipated to be novel binders or substrates of DNA-PKcs, but this will require extensive biological validation.…”
Section: Proof Of Concept�maximizing Extraction Efficiencymentioning
confidence: 99%